Reclaiming local knowledge through saman: A decolonial approach to English literature education - Resti Amalia; Donal Fernado Lubis; Tri Arie Bowo (Universitas Muhammadiyah Banjarmasin, 2026)
Despite increasing international recognition, Indonesian literature remains underrepresented in English Literature classrooms, where Western literary traditions continue to dominate curriculum and pedagogy. This study examines the postcolonial critiques represented in Ayu Utami's Saman and explores its potential as a resource for decolonial pedagogy in English Literature education. Employing a qualitative literary analysis design, the study uses close reading and thematic analysis to examine textual representations of coloniality and social inequality. The findings reveal seven major postcolonial critiques in the novel: colonial mentality, gendered violence, historical amnesia, feudal power structures, religious authority, state violence, and the marginalization of subaltern voices. The novel also portrays various forms of resistance that challenge oppressive political, economic, and cultural structures. These findings demonstrate that coloniality persists beyond formal independence through unequal power relations, institutional control, and the silencing of marginalized communities. Furthermore, the study argues that Saman possesses significant pedagogical value for fostering critical literacy, historical consciousness, epistemic justice, and student agency. By engaging students with local narratives and social realities, the novel can support efforts to challenge epistemic coloniality and advance decolonial approaches to English Literature education in Indonesian higher education.